EFFECTIVE CLONAL MICROPROPAGATION OF MALUS SIEVERSII FROM SEEDS - Yerbolova, L.; Baizhumanova , S.; Rakhatkyzy, A.; Aubakirova, K.; Bakytzhanova , Zh.; Kazybayeva , S.; Kadirsizova , Zh.; Galiakparov, N. (Eurasian Journal of Applied Biotechnology, 2023)
Wild apple tree, Malus sieversii (Ledeb.) M. Roem. is a valuable genetic resource that requires various methods of conservation. The influence of various concentrations of hormones on the regeneration of wild apple from seeds under in vitro conditions was studied to create an optimal regeneration system. Seeds of Malus sieversii, prior to introduction into in vitro culture, were stratified in various substrates for 1,5 months under conditions of low temperature and relatively high humidity to accelerate seed germination and increase their germination. Using various concentrations of hormones, an efficient method for the regeneration of Malus sieversii obtained from seeds in in vitro culture has been optimized. The best indicators of shoot development were on C9 nutrient medium supplemented with 1 mg/l of BAP and NAA, respectively. The introduction of 1.2 mg/l of IAA and 1 mg/l of NAA into the rooting medium resulted in a significant increase in the number of roots, the length of the root and shoot in the studied sample of M. sieversii.